THE ATTITUDES OF INTERNATIONAL STUDENTS IN INDIA TOWARDS ENGLISH - Wildan Mahir Muttaqin (Leksema: Jurnal Bahasa dan Sastra, 2016)
English is now considered as global language, and with every single day its users are increasing numerously. The paper aims to investigate the international students’ attitudes towards English language focusing on a case of International students’ in India. As the central university, The English and Foreign Lnguages (EFL) University India has many international students from a wide range of countries. The attitudes are in language skills and in other perspectives. Upon  the  completion  of  the  collection  of  data,  these  were analyzed,  computed  and  tabulated  using  MS Excel.The study incorporates quantitative approach and has used close ended questionnaire to collect data from the participants. A total number of twenty students participated in the study. From the findings of the data, The research shows that they had  shown  a  positive  attitude  towards  use  of  English  or  an increase  in  the  use  of  English. They believed that learning needs process. Motivation and self-confidence are also main factors to master English comprehensively. They also believe that EFL University is the best place in India to study English intensively.